Back to basics: A re-evaluation of the relevance of imprinting in the genesis of Bowlby’s attachment theory - Robledo, Juan-Pablo; Cross, Ian; Boada-Bayona, Luisa; Demogeot, Nadine (Frontiers in Psychology, 2022)
Attachment theory is one of the key theoretical constructs that underpin explorations of human bonding, taking its current form in John Bowlby's amalgamation of ideas from ethology, psychoanalysis, and developmental psychology. Contemporary research that draws on attachment theory focuses on attachment styles, their impact across the human lifespan and on socio-affectivity; in doing so it overlooks foundational aspects of Bowlby's ideas and their implications for present-day study of attachment in human interactions. This paper attempts to remedy this deficit by exploring the relationships between attachment and imprinting that originally contributed to the development of Bowlby's theories. It critically reviews the theories of imprinting in general, of human imprinting in particular, and of attachment; analysis of the links between these processes bring to the foreground the distinction between supra-individual vs individual aspects of bonding, the relevance of ‘proto’ attachment phases before ‘proper’ Bowlbian attachment is attained, and the neglected role of communicative signals during such early phases. The paper outlines potential benefits of considering such elements in the study of early social cognition, particularly in respect of the study of the gaze and the infant-directed communicative register.